Tipologi Kodifikasi Hadis-Hadis Nabi Muhammad Saw - Moh. Jufriyadi Sholeh (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2020)
Given his position and urgency in religion, the hadiths of the Prophet continued to be guarded by Muslims, so that in the first century of the Hijriyah there was a big idea from the caliph Umar bin Abdul Aziz to collect the hadiths of the Prophet. The Caliph's suggestion was immediately accepted by the scholars, so since then efforts to compile and codify hadith have been carried out. With the support from the government and the sincerity of the scholars in safeguarding this second source of Islamic teachings, the collection of hadiths went well, even in the second, third and fourth centuries of the Hijriyah there was a large-scale codification of hadiths carried out by great hadith scholars. With different typologies in codifying the hadiths of the Prophet, hundreds of thousands of hadiths of the prophet with their sanads were successfully preserved by the scholars in book form. So since then, hadith scholars have focused more on studying hadith through existing hadith books, because hadith books which were codified in the second, third and fourth centuries became the main books of hadith. However, the problem for the novice generation in hadith studies is how to study and trace hadith through these main books, bearing in mind the different typologies of writing. But for those who know the typology, it will be easy to find out the collections that are compiled in one main hadith book. The typologies of the hadith books are, 1) al-Jawámi' which is arranged based on religious themes, 2) as-sunan, al-muwattaha' and mushannaf which are arranged based on fiqh themes, 3) al-masanid which is arranged based on the narrators of the companions and the hadiths collected in one group without classifying the themes, 4) al-ma'ajim compiled based on the musnad of the companions or compiled based on the names of the codifying teachers, based on hijaiyah letter order.